Can peak expiratory flow measurements reliably identify the presence of airway obstruction and bronchodilator response as assessed by FEV1 in primary care patients presenting with a persistent cough?. Issue 12 (1st December 1999) - Thiadens, H A; De Bock, G H; Van Houwelingen, J C; Dekker, F W; De Waal, M W M; Springer, M P; Postma, D S
Abstract : BACKGROUND: In general practice airway obstruction and the bronchodilator response are usually assessed using peak expiratory flow (PEF) measurements. A study was carried out in patients presenting with persistent cough to investigate to what extent PEF measurements are reliable when compared with tests using forced expiratory volume in one second (FEV1 ) as the measure of response. METHODS: Data (questionnaire, physical examination, spirometry, PEF) were collected from 240 patients aged 18–75 years, not previously diagnosed with asthma or chronic obstructive pulmonary disease (COPD), who consulted their general practitioner with cough of at least two weeks duration. The relationship between low PEF (PEF < PEFpred − 1.64RSD) and low FEV1 (FEV1 < FEV1 pred − 1.64RSD) was tested. A positive bronchodilator response after inhaling 400 μg salbutamol was defined as an increase in FEV1 of ⩾9% predicted and was compared with an absolute increase in PEF with cut off values of 40, 60, and 80 l/min and ΔPEF % baseline with cut off values of 10%, 15%, and 20%. RESULTS: Forty eight patients (20%) had low FEV1, 86 (35.8%) had low PEF, and 32 (13.3%) had a positive bronchodilator response. Low PEF had a positive predictive value (PPV) for low FEV1 of 46.5% and a negative predictive value (NPV) of 95%. ΔPEF of ⩾10%, ⩾15%, or ⩾20% baseline had PPVs of 36%, 52%, and 67%, respectively, and ΔPEF of ⩾40, ⩾60, and ⩾80 l/min in absolute terms had PPVs of 39%, 45%, and 57%, respectively, for ΔFEV1 ⩾9% predicted; NPVs were high (88–93%). CONCLUSIONS: Although PEF measurements can reliably exclude airway obstruction and bronchodilator response, they are not suitable for use in the assessment of the bronchodilator response in the diagnostic work up of primary care patients with persistent cough. The clinical value of PEF measurements in the diagnosis of reversible obstructive airway disease should therefore be re-evaluated.